2015
DOI: 10.1080/01647954.2015.1038301
|View full text |Cite
|
Sign up to set email alerts
|

New records of the Lyme disease bacterium in ticks collected from songbirds in central and eastern Canada

Abstract: This study highlights the collection of ticks from wild-caught birds in central and eastern Canada. Using polymerase chain reaction (PCR), 32 (33%) of 98 Ixodes species ticks tested were positive for the Lyme disease bacterium, Borrelia burgdorferi sensu lato (s.l.) Johnson, Schmid, Hyde, Steigerwalt, and Brenner (hereafter B. burgdorferi). Immature blacklegged ticks, Ixodes scapularis Say, which are competent vectors of B. burgdorferi, constituted the predominant Ixodes species tick collected from parasitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 58 publications
4
54
1
Order By: Relevance
“…In addition to mammals, resident and migratory songbirds disperse bird-feeding ticks in the area, especially during northward spring migration [8][9][10][11][12][13][14][15][16][17]. Not only do multiple host species support and maintain Lyme disease vector ticks, Neotropical and southern-temperate songbirds annually transport bird-feeding ticks (i.e., Ixodes affinis, Ixodes minor) into central Canada during spring migration from as far south as Brazil [10,11,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mammals, resident and migratory songbirds disperse bird-feeding ticks in the area, especially during northward spring migration [8][9][10][11][12][13][14][15][16][17]. Not only do multiple host species support and maintain Lyme disease vector ticks, Neotropical and southern-temperate songbirds annually transport bird-feeding ticks (i.e., Ixodes affinis, Ixodes minor) into central Canada during spring migration from as far south as Brazil [10,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Songbirds (Passeriformes) can transport B. burgdorferi s.l.-infected I. scapularis larvae and nymphs to and from this bioregion during bi-directional migration in spring and fall [8][9][10][11][12][13][14][15][16][17]. Peak northward songbird migration in Canada occurs during May and early June, which coincides with peak questing periods of I. scapularis nymphs [47].…”
Section: Ixodes Scapularismentioning
confidence: 99%
“…During spring migration, several Ixodes ticks that originated from southern latitudes have been reported in Canada: an I. minor larva was collected from a Common Yellowthroat, Geothlypis trichas (Linnaeus) [37], I. affinis immatures have be collected from both Common Yellowthroat and Swainson's Thrushes, Catharus ustulatus (Nuttall) [22] [38], and many I. scapularis immatures have been collected from migratory songbirds during spring migration [22] [24] [33] [39]- [41]. Since all of these tick species are songbird-transported ticks, they can be imported into Canada annually during northward spring migration.…”
Section: Dispersal Of B Americana-infected Ticks In North Americamentioning
confidence: 99%
“…Not only are ground-foraging passerine migrants involved with the wide dispersal of immature stages of I. scapularis, raptors are also dispersing agents [27]. In central and eastern Canada, Scott and Durden found that 35% of the songbird-transported I. scapularis nymphs were infected with B. burgdorferi, and widely dispersed in nature [26]. Although global warming is claimed to be one of the contributing factors for enzootic B. burgdorferi transmission and tick expansion, migratory songbirds are actually the principal reason.…”
Section: Climate Change and Songbirdsmentioning
confidence: 99%
“…Moreover, Ogden et al speculates that climate change will induce northward tick expansion of blacklegged ticks in Canada [17], and propagate Lyme disease numbers, but their hypotheses are unsubstantiated. In actuality, the overriding factor in the wide dispersal of I. scapularis and B. burgdorferi in Canada are migratory songbirds [16,[18][19][20]26]. Not only are ground-foraging passerine migrants involved with the wide dispersal of immature stages of I. scapularis, raptors are also dispersing agents [27].…”
Section: Climate Change and Songbirdsmentioning
confidence: 99%